Engagement in community life: perspectives of youths with intellectual and developmental disabilities on families' roles. Issue 20 (24th September 2020) - DuBois, Denise; Renwick, Rebecca; Chowdhury, Mushfika; Eisen, Shauna; Cameron, Debra
Abstract: Purpose: The main objectives of this study were to learn from youths with intellectual and developmental disabilities about the ways their families were involved in their engagement in community life and to capture how they felt about such involvement. Method: The current study is a secondary analysis of a larger study, the Voices of Youths Research Project, framed by inclusive research methods. Thirty-eight semi-structured interviews that discussed perspectives on friendship, social inclusion, and quality of life from 20 participants (ages 13 to 24 years) were included in this paper. All interviews were video-recorded and coded using NVivo 10 . Thematic analysis of the coded segments was guided by a constructivist grounded theory approach. Results: Three major themes emerged from the experiences of youths with intellectual and developmental disabilities on family involvement in their social and community engagement: (1) complex of supports and influences, (2) community engagement with and through family, and (3) points of tension. Conclusions: These thematic findings offer insights into the lived experiences of youths with intellectual and developmental disabilities about engagement in community life. These findings provide an understanding, outside of conventional schemas, of transition into young adulthood for these youths. IMPLICATIONS FOR REHABILITATION: Rehabilitation professionals often work with youths with intellectual and developmental disabilities who face barriers to reaching transition goals identified either by themselves or others. Family members' views that may focus on goals of maximizing functional independence and/or decreasing caregiver demands can often overshadow the goals or views of youths with intellectual and developmental disabilities themselves. Rehabilitation professionals should find ways to explore with youth their family's roles in engagement and belonging in community life so that they can link youths to appropriate community resources and plan optimal interventions/programs. Rehabilitation professionals need to be aware of and respond to points of tension that can emerge between youths with intellectual and developmental disabilities and their family during transition.